Trust in Political Parties, Party Image, and Young Voter Loyalty: The Moderating Role of Digital Literacy among the Community of Renon Traditional Village, South Denpasar District - Veni Yuniati; I.G.A.AG Dewi Sucitawati P; I Nyoman Subanda; Nilna Muna (DAWUH : Islamic Communication Journal, 2026)
The rapid expansion of digital media has fundamentally transformed how young people access, interpret, and evaluate political information, thereby reshaping the determinants of voter loyalty within contemporary digital democracies. This study aims to examine the effects of trust in political parties and party image on young voter loyalty while investigating the moderating role of digital literacy among the community of Renon Traditional Village, South Denpasar District, Bali, Indonesia. A quantitative research design was employed using an online survey administered to 370 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with JASP software. The findings reveal that both trust in political parties and party image have positive and significant effects on young voter loyalty, with party image emerging as the strongest predictor. Furthermore, digital literacy significantly strengthens the relationships between trust in political parties and young voter loyalty as well as between party image and young voter loyalty. These findings suggest that voter loyalty in the digital era is determined not only by the quality of political party representation but also by voters' ability to critically evaluate political information. This study contributes to the voter behavior literature by demonstrating the strategic role of digital literacy as a moderating mechanism that reinforces the influence of trust in political parties and party image on young voter loyalty within the context of contemporary digital democracy.